Evaluation of competency and skills of skilled birth attendants in Madhya Pradesh, central India - Surya Bali; Venkatashiva B Reddy (Indian Journal of Public Health, 2018)
The National Health Mission tracks the proportion of women delivered by skilled birth attendants (SBAs). We assessed SBAs competence in Madhya Pradesh, India, using structured evaluation tools. It is a cross-sectional study conducted from 2014 to 2015. We evaluated 335 trained SBAs using multistage stratified random sampling. Of total, 335 skilled births attendant selected 41.8% were auxiliary nurse midwife, 47.8% were staff nurse, and 10.4% were lady health visitors. Grouping all provider and knowledge test versions, SBAs were correct on 75.4% of the questions. By topic, results ranged from 77.9% correct for the management of normal pregnancy and childbirth to 70.2% correct for intranatal care. The skill evaluation score was 88.1% of infection prevention practices to 74.3% for postnatal care. The present study found significant variations in knowledge and skill competency scores of the SBAs. There is a critical need to improve the training quality of skill birth attendants.